PHARMACOGNOSTICAL EVALUATION OF EMBELIA RIBES AND CAMELLIA SINENSIS: COMPARATIVE STUDIES OF THEIR ANTHELMINTIC ACTIVITY - SEEMA; KUMAR, ARVIND; AGGARWAL, KSHITIZ; KUMAR, ASHOK (International Journal of Current Pharmaceutical Research, 2021)
Objective: The present research work deals with the establishment of a standardization parameter for the Pharmacognositical evaluation of the plant Embelia Ribes and Camellia sinensis. Embelia Ribes is widely using in parasitic intestinal infection, however; Camellia sinensis is mainly used in the beverage preparation, for their Antioxidant activity but their anthelmintic effect is unknown. The present study aims to find out the effect of Camellia sinensis against pheritima Posthuma and compare their anthelmintic effect with Embelia Ribes. Methods: The study has been performed under the different parameters 1). The physicochemical parameter includes total Ash value, acid insoluble ash value, water-soluble ash value, moisture content, and foreign organic matter 2). The phytochemical investigation includes the Extraction of Embelia Ribes and Camellia sinensis in different solvents in the increasing order of their polarity with Petroleum ether, chloroform, ethanol, distilled respectively and showed the presence of Alkaloids, carbohydrates, glycosides, tannins, flavonoids, phenolic compounds. 3) The pharmacological studies include the In vitro anthelmintic effect of Embellia Ribes and Camellia sinensis (ethanolic extract) against Pheritima Posthuma. The paralysis time and death time were studied. Results: Shows the physic-chemical parameters such as total Ash value, acid insoluble ash value, water-soluble ash value, moisture content and foreign organic matter, which was determined to be not more than 8.98%, 1.5%, 7.8%, 3.2% and 0.25% in Embelia ribes as well as 7.78%, 1.6%, 8%, 2.2% and 0.21% in Camellia sinensis. Anthelemintic effect of Embellia ribes and Camellia sinensis (ethanolic extract) were investigated by measuring the paralysis time (75+3.76, 60+4.30, 48+4.40 and 73.32+3.80, 53.34+2.50, 38.55+3.45 respectively) and death time (140+2.82, 135+9.95, 97.55+4.25 and 124.85+5.30, 110.82+5.80, 80.30+2.80) at three different concentration 25 mg, 50 mg, 100 mg, against Pheritima posthuma and compares with the standard drug (Albendazole). Conclusion: Camellia sinensis (ethanolic extract) extract and affords protection against helminthes (Pheritima Posthuma) and results show that Camellia sinensis is as effective as embellia ribes.